Human placenta‐derived matrix with cancellous autograft and demineralized bone matrix for large segmental long‐bone defects in two dogs with septic nonunion. Issue 8 (3rd October 2020) - Kim, Stanley E.; McFetridge, Peter S.; Hagen, Jennifer E.
Abstract: Objective: To report the successful treatment of septic nonunion in two dogs with large segmental defects secondary to long‐bone fractures by using a novel human placenta‐derived matrix (hPM) as adjunct to fixation. Animals: One 3‐kg 9‐year‐old neutered male Yorkshire terrier with a distal antebrachial fracture and one 6‐kg 4‐year‐old spayed female miniature pinscher with a distal humeral fracture. Study design: Short case series. Methods: Both dogs presented for septic nonunion after internal fixation of Gustilo type II open diaphyseal fractures from dog bite injuries. During revision, debridement of nonviable bone resulted in segmental defects of 32% and 20% of the bone length for the antebrachial and humeral fractures, respectively. The antebrachial fracture was stabilized with a circular external fixator, and the humeral fracture was stabilized with biaxial bone plating. The fracture sites were not collapsed, and full length was maintained with the fixation. Autogenous cancellous bone graft and canine demineralized bone allograft were packed into the defects, and hPM was injected into the graft sites after closure. Results: Radiographic union was documented at 8 weeks and 6 weeks for the antebrachial and humeral fractures, respectively. Both dogs became fully weight bearing on the affected limbs and returned to full activity. Conclusion: Augmenting fixation with grafts and hPM led to a relatively rapid union in both dogs reported here.